2018
DOI: 10.1038/s41598-018-30834-7
|View full text |Cite|
|
Sign up to set email alerts
|

Improving Stem Cell Delivery to the Trabecular Meshwork Using Magnetic Nanoparticles

Abstract: Glaucoma is a major cause of blindness and is frequently associated with elevated intraocular pressure. The trabecular meshwork (TM), the tissue that primarily regulates intraocular pressure, is known to have reduced cellularity in glaucoma. Thus, stem cells, if properly delivered to the TM, may offer a novel therapeutic option for intraocular pressure control in glaucoma patients. For this purpose, targeted delivery of stem cells to the TM is desired. Here, we used magnetic nanoparticles (Prussian blue nanocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…Although some ADSCs were attached to the iris and corneal endothelium, they did not induce obvious ocular abnormalities. Using magnetic nanoparticles to improve stem cell homing 46 might be a good option to further increase the efficiency of ADSC homing and integration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some ADSCs were attached to the iris and corneal endothelium, they did not induce obvious ocular abnormalities. Using magnetic nanoparticles to improve stem cell homing 46 might be a good option to further increase the efficiency of ADSC homing and integration.…”
Section: Discussionmentioning
confidence: 99%
“…We have successfully induced ADSCs to differentiate into corneal keratocytes, 45 a cell type derived from neural crest, and thus, sharing the same embryonic origin as TM cells. Snider et al 46 reported that adipose‐derived MSCs can be specifically delivered to the TM tissue using magnetic nanoparticles, which suggests the feasibility of using ADSCs for TM regeneration. Here, we demonstrate that ADSCs can be induced to differentiate into TM‐like cells (ADSC‐TM) with characteristics of TM cells, namely gene expression patterns, response to dexamethasone (DEX) stimulation, phagocytic capacity, and ability to maintain aqueous humor dynamics in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Using enucleated tissue CP injuries can only be tracked for a few hours after injury creation. For assessing multi-day or multi-week time courses an alternative approach will be needed where anterior tissue can be maintained long term post-enucleation, such as in organ culture [41][42][43][44][45] , or by transitioning to an animal model. Another limitation is the eye holder housing the eye in gelatin is uniformly shaped and thus does not exactly mimic the complex geometry of the ocular orbit.…”
Section: Discussionmentioning
confidence: 99%
“…Human adipose-derived mesenchymal stem cells (MSCs; Lonza) were labeled with PBNCs using previously reported methods, 4 and minimal impact on stem cell viability and multipotency following labeling was observed through in vitro assessments, which are commonly performed to independently assess nanoparticle impact on cellular function and anticipate effects in vivo . 25 Briefly, at roughly 80% confluence, MSCs were incubated with PBNC-containing media overnight. PBNCs were dispersed in the media at an optical density of 2, corresponding to roughly of media.…”
Section: Methodsmentioning
confidence: 99%